ANALISIS KONTRIBUSI DAN EFEKTIVITAS PAJAK DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAHKOTA SURABAYA - ARDITIA, REZA (Jurnal Akuntansi AKUNESA, 2013)
This research aims to determine the contribution of each post to the local tax revenueand the effectiveness of each postal receipts tax Surabaya area. Analysis is conducted using aqualitative method of ratio, the ratio of contributions to calculate the contribution of eachpost to the local tax revenue during the years 2007-2011, and the ratio of effectiveness todetermine the level of the city of Surabaya in the realization of the target from each post localtax. From the analysis of the data can be seen that: First, street lighting tax revenuecontributed most to the city of Surabaya that is with an average of 17.25 percent. Second, theeffectiveness of each local tax Surabaya heading into the category of less effective, fairlyeffective, effective and very effective with effectiveness ratios ranged from 71.61 percent tomore than 100 percent.Keywords: local taxes, local revenues, contributions, effective